BATTLE OF THE THREE SINGAPORE LOCAL BANKS IN THE CREDIT CARD INDUSTRY: SINGAPORE LADIES CARD MARKET - Wee, Eileen (2006)
'War belongs to the province of business competition, which is also a conflict of human interests and activities.' Karl von Clausewitz, On War